5(x-3)=2(7x-3)

Simple and best practice solution for 5(x-3)=2(7x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)=2(7x-3) equation:



5(x-3)=2(7x-3)
We move all terms to the left:
5(x-3)-(2(7x-3))=0
We multiply parentheses
5x-(2(7x-3))-15=0
We calculate terms in parentheses: -(2(7x-3)), so:
2(7x-3)
We multiply parentheses
14x-6
Back to the equation:
-(14x-6)
We get rid of parentheses
5x-14x+6-15=0
We add all the numbers together, and all the variables
-9x-9=0
We move all terms containing x to the left, all other terms to the right
-9x=9
x=9/-9
x=-1

See similar equations:

| 9(e+3)-6=3(e-4)-15 | | 4(4x+4)-5(3x-1)=21 | | 9(k-2)+1=2(k+2)+7 | | 8(h-1)-10=3(h+4)+5 | | 2x+10=1-x | | 9(n-3)-6=2(n+4)+29 | | -x+20=25 | | 5x=5=2x=2 | | 3(r+2)+4=r-14 | | 40=3x+13= | | 3(1-n)+16=n-25 | | 3r-4=r-2 | | 3=-2*(x+6,5) | | x–4=–8 | | x2+4x-38=-4x-5 | | 6(5x-4)+4(3x-6)=162 | | 5^{2x}-5^{x+1}+6=0 | | 11k-17=4k+11 | | 8w-5=2w+1 | | 2d+10=4d-4 | | 2a-4+5a-7+3a=10a+11 | | 31=-3v-7v | | x2-9x+7=-4x+3 | | 8.24=x/4/2 | | 6h+22=2h-26 | | N(n+1)=272 | | 6=20k-8 | | 5a+7-3a-2=2a+5 | | 9r-10=4r+5 | | 7=19+4d | | 6-4z=-6 | | 7p-2p=18+7 |

Equations solver categories